Pengelolaan Sampah yang Berwawasan Lingkungan dalam Aspek Hukum: Kajian terhadap Problematika Keberadaan Tempat Penampungan Sementara (TPS) Deli Serdang - Yopi, Mhd. Hafiz Fahrezy; Sembiring, Elvina Br; Simanjuntak, Novita Sarah; Girsang, Roma Nanda; Sitompul, Agnes Olivia; Gaol, Anggelina Labora Dorasi Lumban; Ramadhan, Taufiq (Indo-MathEdu Intellectuals Journal, 2026)
Indonesia is the second largest waste producing country in the world after China. However, the bad news is that this country, which is rich in natural resources, cannot manage its waste properly. Not only at the national level, poor waste management also occurs in various cities in Indonesia. Therefore, this study aims to determine how environmentally sound waste management is carried out in legal aspects by studying the problems of the Deli Serdang Temporary Shelter (TPS). Various problems were found, namely the distance between the Deli Serdang Temporary Shelter (TPS) is very close to residential areas, this is certainly very disturbing to the activities of surrounding residents because water and air pollution caused by this TPS not only disturbs residents' activities but also becomes a source of disease. The method used in this study is the Descriptive Qualitative method, where the author will reveal a phenomenon by describing data and facts through words comprehensively in this case related to waste management at the Deli Serdang Temporary Shelter (TPS) seen from the Legal Aspect. The output of this research is in the form of a Final Research Report which is also accompanied by a Journal Article so that the results of this research can be read by more people and can obtain Intellectual Property Rights